(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The human intestinal tract has been colonized by thousands of species of bacteria during the coevolution of man and microbes. Evidence for various beneficial roles of the intestinal microbiota in human health and disease is expanding rapidly. The health benefits imparted by the synbiotics have been the subject of extensive research in the past few decades. A synbiotic product beneficially affects the host in improving the survival and implantation of live microbial dietary supplements in the gastrointestinal tract by selectively stimulating the growth and activating the metabolism of one or a limited number of health-promoting bacteria.